The social market economy : relationship with christian social thought and implications for the latin american case - Resico, Marcelo Fernando (2010)
Fil: Resico, Marcelo F. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina